De facto currency baskets of China and East Asian economies: The rising weights - Ying Fang; Shicheng Huang; Linlin Niu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
We employ Bayesian method to estimate a time-varying coefficient version of the de facto currency basket model of Frankel and Wei (2007) for the RMB of China, using daily data from February 2005 to July 2011. We estimate jointly the implicit time-varying weights of all 11 currencies in the reference basket announced by the Chinese government. We find the dollar weight has been reduced and sometimes significantly smaller than one, but there is no evidence of systematic operation of a currency basket with discernable pattern of significant weights on other currencies. During specific periods, the reduced dollar weight has not been switched to other major international currencies, but to some East Asian currencies, which is hard to explain by trade importance to or trade competition with China. We examine currency baskets of these East Asian Economies, including major international currencies and the RMB in their baskets. We find an evident tendency of Malaysia and Singapore to increase the weights of RMB in their own currency baskets, and a steadily and significantly positive weight of RMB in the basket of Thailand. These evidences suggest that, the positive weights of some East Asian currencies in RMB currency basket during specific periods largely reflect the fact that these East Asia economies have been systematically placing greater weights on RMB under the new regime of RMB exchange rate.
URN:NBN:fi:bof-201408072040
Keywords: F31; F41; C11; 330; RMB currency basket; time-varying regressions; East Asia; China; US